Epidemiological Profile of Intimate Partner Homicides of Sexual and Gender Minority Women in the United States, 2003 to 2017 - Anderson, Elizabeth J (Journal of interpersonal violence, 2023)
Sexual and gender minority (SGM) women are among the many victims killed by intimate partner homicide (IPH) each year, though the differences between different SGM groups (and how these groups compare to non-SGM IPH) have not been well established. The objective of this article was to identify practicable, correlated risk factors of IPH of SGM women that may have utility in prevention of future IPH among these populations in the U.S. Homicide data from the National Violent Death Reporting System spanning 2003 to 2017 were used to identify a profile of IPH specific to SGM women compared to women who were neither sexual nor gender minorities. Situational and individual characteristics significantly differentiated sexual minority (SM) women from non-SGM women victims of IPH, including substance abuse history (adjusted odds ratio [AOR] = 4.80 [2.42, 9.51]), having themselves used a weapon during the incident (AOR = 3.63 [1.44, 9.16]), and the type of weapon(s) used, such as firearms (AOR = 0.61 [0.40, 0.91]), with notably different differentiating characteristics for gender minority (GM) women (vs. non-SGM women) such as the likelihood that the victim was known to have experienced interpersonal violence victimization in the previous month (AOR = 0.50 [0.07, 3.67]). Lesbian and bisexual women homicide victims were far more likely to have been killed via IPH than non-SGM women (AOR for Black SM women = 7.84 [3.65, 16.88], AOR for White SM women = 2.30 [1.03, 5.17]). There was no corresponding difference for GM women victims, whose likelihood of being killed by an intimate partner was similar to that of non-SGM women. Based on these findings, actionable public health recommendations—centered around evidence that neither “all women” nor “all LGBTQ people” are appropriate intimate partner violence prevention umbrellas—are proposed.